FAKTOR RISIKO KEJADIAN ASMA PADA ANAK DI KOTA PADANG - Mangguang, Masrizal Dt (ARCHIVE OF COMMUNITY HEALTH; Vol 3 No 1 (2016): Juni (2016), 2016)
Asthma is a chronic disease that is often found in children. Based on the National Health Survey  (RISKESDAS) in Indonesia, the prevalence of asthma in the Province of West Sumatra was 3,6%, this is relatively high compared to other provinces. The incidence of asthma among children(1-14 years old)  in the Public Health Center (PHC) of Pauh was 6% higher compared to other PHCs. This study aimed to identify risk factors associated with the incidence of asthma among children in Pauh Public Health Center. This study used a case-control study and included 1-14 year old children with asthma who visited PHC of Pauh  as case and 1-14 year old children without asthma who visited PHC of Pauh as control. The number of samples in the case group were 32 and control group were 64. Data analysis included univariate, bivariate with the chi-square test and multivariate analysis with multiple logistic regression methods. The risk factors that independently associated with asthma were male (OR=5.2; 95%CI: 1.5-17.9), not exclusive breastfeeding (OR=4.2; 95%CI: 1.2-14.7), family history of asthma (OR=10.8; 95%CI: 3.3-35.1), and contact with pets (OR=8.5; 95% CI: 1.3-54.9). Boys with a family history of asthma need more attention because of their higher risk. Prevention is advised to  start since birth through early lactation initiation and followed by exclusive breastfeeding. Family participation in the prevention of asthma is warranted since they have a big role in minimizing their child’s contact with animals.
Keywords: asthma in children, risk factors